The impact of smart applications on the performance of the operational manager in the retail sector in some of the major private retail sectors in Jordan and Saudi Arabia for the year 2024 - Muaz, Mutaz Muaz (Mohammed Hafez) (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to demonstrate the extent of the impact of smart applications on the performance of operational managers in the retail sector in some of the largest private retail sectors in Jordan and Saudi Arabia for the year 2024. It also aimed to reveal, through the study sample, the relationship between the independent variable, which is smart applications, and its impact on the efficiency and role of operational managers, by relying on an applied study that relied on the descriptive analytical approach. A comprehensive survey was applied to the study sample, which is operational managers and operational supervisors in operational management in Jordan and Saudi Arabia, through a questionnaire as a tool for collecting data, as 200 questionnaires were distributed. The study reached several results, the most important of which is the presence of a positive and significant impact of smart applications through smart algorithms. It recommended the need to work on balancing between the operational manager as an official who relies on human feeling and smart applications that deal with algorithms and inputs and give evaluations without taking into account the human sense aspect. Here, companies must continue to support operational managers with comprehensive training that covers all aspects of using applications that open new horizons in retail markets and enhance the efficiency and control process of senior management over operational managers working within hypermarkets.
Keywords: Smart Apps; Retail Stores Operations Manager